2021
DOI: 10.1097/md.0000000000024955
|View full text |Cite
|
Sign up to set email alerts
|

Using arterial spin labeling blood flow and its histogram analysis to distinguish early-stage nasopharyngeal carcinoma from lymphoid hyperplasia

Abstract: To investigate the feasibility of arterial spin labeling (ASL) blood flow (BF) and its histogram analysis to distinguish early-stage nasopharyngeal carcinoma (NPC) from nasopharyngeal lymphoid hyperplasia (NPLH). Sixty-three stage T1 NPC patients and benign NPLH patients underwent ASL on a 3.0-T magnetic resonance imaging system. BF histogram parameters were derived automatically, including the mean, median, maximum, minimum, kurtosis, skewness, and variance. Absolute values were obtained for skewn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…First-order features and analysis, which are relatively easier to understand and implement compared with radiomics, reflect the distribution of voxel intensity with high reproducibility [19,20]. Previous studies [21][22][23][24] showed that whole-tumour first-order features, such as Skewness, Variance and so on, can potentially be used for diagnosis and survival prediction in NPC. The research in SyMRI demonstrated that Mean value could help in discriminating NPC from NPH, but the test-retest repeatability and tumour heterogeneity were not evaluated [13].…”
Section: Introductionmentioning
confidence: 99%
“…First-order features and analysis, which are relatively easier to understand and implement compared with radiomics, reflect the distribution of voxel intensity with high reproducibility [19,20]. Previous studies [21][22][23][24] showed that whole-tumour first-order features, such as Skewness, Variance and so on, can potentially be used for diagnosis and survival prediction in NPC. The research in SyMRI demonstrated that Mean value could help in discriminating NPC from NPH, but the test-retest repeatability and tumour heterogeneity were not evaluated [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, perfusion weighted MR imaging (PWI) allows to assess cancer tissue vascular properties and has the potential to significantly improve the accuracy of MRI in HNSCC evaluation both for diagnosis and prognosis [ 6 ]. Dynamic contrast enhanced (DCE) MRI, based on the serial acquisition of multiple T1-weighted images before, during and after the intravenous injection of a Gd-based contrast agent, is the most frequently used perfusion technique for H&N region, though other perfusion techniques such as dynamic susceptibility contrast (DSC) and arterial spin labeling (ASL) have been proposed [ 7 9 ]. The rationale for using PWI in HNSCCs evaluation lies in the possibility of evaluating tumor neoangiogenesis.…”
Section: Introductionmentioning
confidence: 99%